Capacity of Social Institutions: Towards Participation in Community-Centered Management Programs - Abtin Heidarzadeh; Mehrdad Farrokhi; Jafar Bazyar; Negar Pourvakhshoori (International Journal of Preventive Medicine)
The new managerial approach demands the profound examination of capacities, resources, and facilities in social institutions and organizations and optimum and systemic utilization of capacities such as individuals’ abilities, expertise, and skills within the framework of social institutions. This approach will thus empower the community, which is the most appropriate platform for sustainable development, and improve systemic and integrated management. The study is designed systematically to identify the capacities of social institutions to empower the existing capacities and plan management and educational programs in a better manner to use these capacities within communities. This systematic review study is conducted until February 15, 2024. The PRISMA system was used to track the review process and findings. Databases were searched for relevant articles, and the STROBE checklist was used to evaluate the quality of the articles. The community-based social organizations will still face budgetary challenges and costs in their capacity-building efforts. As such, advanced management techniques such as teamwork, collaboration and coordination between departments, innovative thinking, brainstorming, or even the use of program evaluation and analytical actions can help reduce possible challenges. This calls for the availability of exact management models and planners in both government systems and people-centered systems to coordinate such capacities. This will seek to shed more light on the important role of social institutions and hence serve to give a clearer understanding of challenges, opportunities, and supportive actions for such institutions to contribute to better government system management.